Our cups are full : pottery and society in the Aegean Bronze Age : papers presented to Jeremy B. Rutter on the occasion of his 65th birthday - Gauss, Walter, 1969-; Lindblom, Michael; Smith, R. Angus K. (Robert Angus K.), 1968-; Wright, James C., 1946-; Rutter, Jeremy B. (Archaeopress, 2011)
This is a collection of papers presented to Jeremy Rutter to mark his 65th birthday.